Three-Photon Adaptive Optics for Mouse Brain Imaging - Sinefeld, David; Xia, Fei; Wang, Mengran; Wang, Tianyu; Wu, Chunyan; Yang, Xusan; Paudel, Hari P.; Ouzounov, Dimitre G.; Bifano, Thomas G.; Xu, Chris (Frontiers in Neuroscience, 2022)
Three-photon microscopy (3PM) was shown to allow deeper imaging than two-photon microscopy (2PM) in scattering biological tissues, such as the mouse brain, since the longer excitation wavelength reduces tissue scattering and the higher-order nonlinear excitation suppresses out-of-focus background fluorescence. Imaging depth and resolution can further be improved by aberration correction using adaptive optics (AO) techniques where a spatial light modulator (SLM) is used to correct wavefront aberrations. Here, we present and analyze a 3PM AO system for in vivo mouse brain imaging. We use a femtosecond source at 1300 nm to generate 3-photon (3P) fluorescence in yellow fluorescent protein (YFP) labelled mouse brain and a microelectromechanical (MEMS) SLM to apply different Zernike phase patterns. The 3P fluorescence signal is used as feedback to calculate the amount of phase correction without direct phase measurement. We show signal improvement in the cortex and the hippocampus at greater than 1 mm depth and demonstrate close to diffraction-limited imaging in the cortical layers of the brain, including imaging of dendritic spines. In addition, we characterize the effective volume for AO correction within brain tissues, and discuss the limitations of AO correction in 3PM of mouse brain.